FAKTOR-FAKTOR YANG MEMPENGARUHI KETERTARIAKAN NASABAH DALAM PEMBELIAN PRODUK ASURANSI KENDARAAN BERMOTOR - Harahap, Nurhayati; Nabila, Dara Nabila; Sari, Novita; Dwita Putri, Riri (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Motor vehicle insurance policy is a type of contract that outlines the legal relationship between an insurance company (insurer) and an insurance customer (insured). Throughout 2024, the number of traffic accidents in Indonesia increased drastically. As of August 5, 2024, 79,220 traffic accidents were reported, based on data from the Integrated Road Safety Management System (IRSMS) of the Indonesian Police Traffic Corps. When compared to the previous period, these statistics show an alarming spike. same as the previous year.The aim of this research is to determine the variables that influence consumers' desire to buy motor vehicle insurance. Vehicle insurance is very important for protection in facing increasingly complicated traffic conditions and high risk of accidents. The literature review method, namely collecting and reviewing various related literature to determine the elements that influence consumer interest, was used in this research. Based on the study's findings, there are three main factors that significantly influence the results: product quality, price, and religiosity. Customers are more interested in car insurance when the product is of high quality and affordable prices. Apart from that, the choice of more religious customers towards insurance products that suit their views is influenced by elements of religiosity, especially those related to sharia principles. It is hoped that these results can serve as a guide for insurance businesses in creating products and marketing plans that are more suited to the needs and tastes of their clients.